Between Scylla and Charybdis: CEO political ideology, dividends and downsizing during the pandemic - Ali Bayat; Marc Goergen; Panagiotis Koutroumpis; Xingjie Wei (Queen Mary University of London, School of Economics and Finance, 2022)
We study whether CEO political ideology affected how S&P 500 firms reacted to the Covid-19 pandemic, an exogenous shock to demand and supply. We hypothesize that conservative CEOs are more likely to adopt shareholder-friendly than employee-friendly reactions to the pandemic. Hence, they should be more likely to downsize their workforce while maintaining dividends. In contrast, other CEOs should be less likely to meet dividend expectations and less likely to downsize. We find confirmation of this hypothesis. We also find that CEOs used the dividend forecasts for 2020 as their benchmark rather than the 2019 dividends to make their dividend decision.
Keywords: G35; G34; M51; 330; CEO political ideology; dividend policy; downsizing; stakeholder management; Covid-19